Money talks - Die Internationalisierung des Marktes für Büroimmobilien in Ostmitteleuropa.: Das Beispiel Warschau - Pütz, Robert (ERDKUNDE, 2001)
Since the beginning of the 1990s the office market in the large cities of East Central Europe has been characterised by the confrontation of two major development trends: the transformation processes from the state controlled economy to the market economy, as their core components can be seen as a fundamental restructuring of the institutions, and the changes in the international real estate market accompanied by fundamental new orientation of investment strategies and transactions between the market participants. With the coming together of both these factors, the office markets in East Central Europe have flourished dynamically in a way unprecedented on an international level, and accompanied by profound effects on the city structure. Taking Warsaw as an example, the following work explains that model transformation processes in the office market occur in three phases. For each of these phases, specific combining effects of institutional framework conditions and local regulation mechanisms can be identified, as well as a specific degree of (advanced) internationalisation and a respective characteristic player constellation, which correspond with respective different market developments and significance of locations.